2022
DOI: 10.1002/ece3.8670
|View full text |Cite
|
Sign up to set email alerts
|

Seed dormancy varies widely among Arabidopsis thaliana populations both between and within Fennoscandia and Italy

Abstract: The timing of germination is a key life‐history trait in plants, which is strongly affected by the strength of seed dormancy. Continental‐wide genetic variation in seed dormancy has been related to differences in climate and the timing of conditions suitable for seedling establishment. However, for predictions of adaptive potential and consequences of climatic change, information is needed regarding the extent to which seed dormancy varies within climatic regions and the factors driving such variation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…4B , D , F ). Previous work at the study site has shown that the Italian and Swedish genotypes differ in their annual seed dormancy cycle, with the Swedish genotype releasing its seed dormancy earlier compared to the Italian genotype ( Postma et al , 2016 ; Zacchello, 2021 ), and that this is associated with earlier germination ( Postma and Ågren, 2018 ; see also Fig. 2A ).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…4B , D , F ). Previous work at the study site has shown that the Italian and Swedish genotypes differ in their annual seed dormancy cycle, with the Swedish genotype releasing its seed dormancy earlier compared to the Italian genotype ( Postma et al , 2016 ; Zacchello, 2021 ), and that this is associated with earlier germination ( Postma and Ågren, 2018 ; see also Fig. 2A ).…”
Section: Discussionmentioning
confidence: 78%
“…Interestingly, by the end of the germination period in the 2013 experiment, the mean proportion of seeds that had germinated in the RIL population was higher than that of the two parental genotypes. The Italian and Swedish genotypes differ in the timing of their annual seed dormancy cycles ( Postma et al , 2016 ; Zacchello, 2021 ), and the among-year variation in germination proportion of different genotypes may reflect differences in the match between the timing of dormancy release and seasonal changes in conditions for germination, as suggested by the conceptual model illustrated in Fig. 4B , D and F .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We developed a set of high‐quality occurrence data (i.e. species ID verified and location checked, N = 4024) from published research (Durvasula et al, 2017; Hsu et al, 2019; Mandáková et al, 2017; Zacchello et al, 2022; Zeng et al, 2017; Zou et al, 2017), publicly available herbarium and germplasm accessions with known collection locations (Alonso‐Blanco et al, 2016; DeLeo et al, 2020), and some of our recent field collections in East Africa (Gamba et al, 2022). These span a period of 1794–2018.…”
Section: Methodsmentioning
confidence: 99%
“…Seed dormancy is an adaptive trait that evolved to enhance seedling survival by avoiding germination under unsuitable environmental conditions (Liu et al 2019a; Iwasaki et al 2022). Dormancy varies between species, clades, communities, and regions and is regulated by both internal and external factors (Zacchello et al 2022; Pausas and Lamont 2022). That is, dormancy results from genetic and environmental factors and their interactions.…”
Section: Introductionmentioning
confidence: 99%